2019
DOI: 10.1021/acs.iecr.8b05535
|View full text |Cite
|
Sign up to set email alerts
|

Novel All-Natural Material for Oil/Water Separation

Abstract: Traditional oil/water separation materials were prepared with partial or all nonrenewable raw materials, which would not only increase resource consumption but also cause new environmental pollution after being abandoned. In this work, a superhydrophobic and superoleophilic oil/water separation all-natural material was prepared using a simple and fast emulsion immersing method. The raw materials used including natural sponges and natural vegetable waxes, all of which are renewable. The as-prepared all-natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…6 When natural fibers are used, being hygroscopic, a compromise in the selectivity of the absorbent is evident. 17,18…”
Section: Introductionmentioning
confidence: 99%
“…6 When natural fibers are used, being hygroscopic, a compromise in the selectivity of the absorbent is evident. 17,18…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the Lotus leaf is an incredible example of the plants that have natural superhydrophobic surfaces [16] . The detailed study has shown that the lotus leaf has possessed superhydrophobicity due to the low surface energy wax layer and the surface roughness generated by microstructures [17] . Inspired by nature, several efforts are made to develop synthetic superhydrophobic surfaces for oil/water separation [18,19] .…”
Section: Introductionmentioning
confidence: 99%
“…Traditional oil-water separation materials are mostly prepared from nonrenewable raw materials, which not only increases the consumption of resources but also causes further environmental pollution after abandonment [6]. In addition, the process of preparing organic synthetic products is sophisticated and costly.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies have been conducted on oil cleaning using natural materials, such as cotton [5,[9][10][11], kapok fiber [5,11], peat [12], wheat and barley straw [13,14], palm tree leaves or pith waste [15,16] banana trunk fibers [16,17], different cellulose-based materials [18,19], and natural sponge [6], among others. For sustainable and effective oil spill treatment, bio-based materials should be studied extensively, as one material is unlikely to be suitable in all possible oil spill scenarios [8].…”
Section: Introductionmentioning
confidence: 99%